Determination of the dependence of the NPP unit power on the steam temperature at the outlet of the superheater separator first stage with an uncertainty of information - Yefimov, O.V.; Potanina, Т.V. (Вопросы атомной науки и техники, 2022)
The article discusses the application of the standard statistical approach and interval analysis procedures to the estimation of the parameters of the dependence of the power of an NPP power unit on the steam temperature at the outlet of the first stage of the superheater separator under conditions of measurements noise, unknown probabilistic characteristics of errors and with a short measurements sample. The influence of reducing the error in determining the power of the power unit on the choice of the experiment result processing method is investigated. The situation of measurement error limitation without reliable information about its distribution is considered. The correctness of the application of interval analysis numerical methods for processing experimental data under conditions of uncertainty and a significant decrease in the maximum value of the total error is shown. The data were approximated by the Levenberg-Marquardt minimization method when the relative error of the measurement results equaled 5%. Розглянуто застосування стандартного статистичного підходу і апарату інтервального аналізу до оцінки параметрів залежності потужності енергоблоку АЕС від температури пари на виході з першого ступеня сепаратора-пароперегрівника в умовах невизначеності інформації: наявності «шуму» у вимірах, невідомих ймовірнісних характеристиках похибок та достатньо малій вибірці спостережень. Досліджується вплив зменшення похибки визначення потужності енергоблоку на вибір методу обробки результатів експерименту. Розглядається ситуація обмеженості похибки вимірювань без достовірної інформації про її розподіл. Показана коректність застосування чисельних методів інтервального аналізу для обробки експериментальних даних в умовах невизначеності та зменшення максимального значення сумарної похибки. При стандартній 5% відносній похибці результатів вимірювань застосовано апроксимацію даних методом мінімізації Левенберга-Марквардта. Рассматривается применение стандартного статистического подхода и аппарата интервального анализа к оцениванию параметров зависимости мощности энергоблока АЭС от температуры пара на выходе из первой ступени сепаратора-пароперегревателя в условиях неопределенности информации: наличия «шума» в измерениях, неизвестных вероятностных характеристиках погрешностей и при достаточно короткой выборке наблюдений. Исследуется влияние уменьшения погрешности определения мощности энергоблока на выбор метода обработки результатов эксперимента. Рассматривается ситуация ограниченности погрешности измерений без достоверной информации о ее распределении. Показана корректность применения численных методов интервального анализа для обработки экспериментальных данных в условиях неопределенности и существенного уменьшения максимального значения суммарной ошибки. При стандартной 5% относительной погрешности результатов измерений выполнена аппроксимация данных методом минимизации Левенберга-Марквардта.